1994
DOI: 10.1007/bf00190104
|View full text |Cite
|
Sign up to set email alerts
|

The extravascular contractile system in the human placenta

Abstract: In the human placenta, besides the fetal blood vessel system a second extravascular contractile system exists. It is localized in the chorionic plate and runs in a longitudinal direction and adjacent to fetal blood vessels into the stem villi, where it forms perivascular contractile sheaths. Characteristically, cells of the extravascular contractile system are extremely long and spindle-shaped and give rise to fine cell processes, by which they obviously contact each other or insert into the basement membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In 1922, Naujoks (11) proposed the hypothesis that the human placenta is capable of contraction and Krantz and Arey (11) later demonstrated that these cells in the placenta have all the morphological characteristics of smooth muscle. More recently, Graf et al (5) confirmed the presence of myofibroblasts in stem villi by demonstrating the immunolocalization of vimentin, desmin, ␣-actin, ␥-actin, and myosin in these cells (5). Those investigators also proposed that the change in villus length is an active process (5).…”
Section: Discussionmentioning
confidence: 96%
“…In 1922, Naujoks (11) proposed the hypothesis that the human placenta is capable of contraction and Krantz and Arey (11) later demonstrated that these cells in the placenta have all the morphological characteristics of smooth muscle. More recently, Graf et al (5) confirmed the presence of myofibroblasts in stem villi by demonstrating the immunolocalization of vimentin, desmin, ␣-actin, ␥-actin, and myosin in these cells (5). Those investigators also proposed that the change in villus length is an active process (5).…”
Section: Discussionmentioning
confidence: 96%
“…The exclusion of fibroblasts has been facilited by using chorioplacental vessels instead of intravillous vessels, which are known to present a gradient of differentiation from fibroblast to myofibroblast extending from the trophoblast to the axial vessels. The deepest cells form sheaths surrounding the vessels (Graf et al 1995). The CAM cultured in this study derived from the media of chorioplacental arteries, since the adventitia, which contains fibroblasts, was removed by forceps.…”
Section: Discussionmentioning
confidence: 99%
“…Graf et al (1994) [5] have described "perivascular contractile sheaths" in the stem villi, also called "extra-vascular contractile system". Ultrastructural studies have suggested the association at this level of smooth muscle cells and subpopulations of microfibroblasts differentited from the perivascular mesenchimal stroma [26,27].…”
Section: Pre-sinusoid Sphincters In the Mature Intermediate Villi Systemmentioning
confidence: 99%
“…Initially the cells similar to those in the smooth muscle were defined [1][2][3][4] and later these contractile elements were integrated in the "extra-vascular contractile system'' at the level of stem villi, associated with the extra-cellular matrix of villose stroma [5,6]. The correlations between smooth muscle cells and the elastic fibres with the collagen fibres in a myofibroelastic anatomical-functional unit are well known [6].…”
Section: Introductionmentioning
confidence: 99%